Metode Speos (Stimulasi Pijat Endorphin, Oksitosin dan Sugestif) Dapat Meningkatkan Produksi ASI dan Peningkatan Berat Badan Bayi - Nugraheni, Diah Eka; Heryati, Kosma (Jurnal Kesehatan, 2017)
Target of achieving exclusive breastfeeding is 33.6%, still low (IDHS 2010). Exclusive breastfeeding is intended to guarantee the fulfillment of the right of infants to 6 months old, with attention to growth and development, so that every mother would give exclusive breastfeeding to baby (PP no.23, 2012), the problem is that the milk does not come out in the first day of birth. It should be anticipated since pregnancies through lactation counseling, but the dissemination of information among the officers have not been optimized, so it was needed an alternative ways of stimulating milk production (Wiwin W, 2014). This study aims was to determine the SPEOS methods to increase milk production and baby weight.This research design used Quasi Experiment. Sample were primiparous postpartum mothers who were given the intervention SPEOS methods on the first day postpartum, were began 1-6 hours until the fourth week, then milk production measured before and after the intervention to see milk production and an increase in baby weight. The data analysed univariat analysis, Wilcoxon test bivariate analysis, multivariate analysis, and ANCOVA analysis to control confounding factors. This results showed the method SPEOS effect on milk production, average of 131.87 (p=0.00) and increased infant weight, average of 483.30 g (p 0.00). Age and the food consumed by the mother during the study (maternal nutrition) did not affect milk production, whereas IMD effect on milk production with 0.389 square r (p 0.04). SPEOS methods effect on milk production and an increase in baby weight on postpartum mother in Bengkulu City in BPM, 2016. Expected to all health workers can use the SPEOS method as a standard procedure in stimulate milk production to increase exclusive breastfeeding targets.